2023
DOI: 10.3389/fpubh.2023.1191699
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practice of healthcare workers on early gastrointestinal cancer in China

Abstract: ObjectiveGastrointestinal cancer is the leading cause of cancer-related death in China, and its early screening is largely recommended by healthcare workers. This study investigated the knowledge, attitudes, and practice (KAP) of healthcare workers on early gastrointestinal cancer (EGC).MethodsThis cross-sectional study was conducted on healthcare workers who volunteered to participate from 30 hospitals in China between September and December 2022. A self-administered questionnaire including 37 questions was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
2
1
0
Order By: Relevance
“…Moreover, the study found that attitude mediated between knowledge and practice, indicating that attitude influenced knowledge translation into behavior. These findings were consistent with the KAP theoretical model and previous findings [ 29 , 30 ]. According to the KAP model, dietary behavioral changes in HD patients involved three successive processes: knowledge acquisition, belief generation, and behavior formation.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the study found that attitude mediated between knowledge and practice, indicating that attitude influenced knowledge translation into behavior. These findings were consistent with the KAP theoretical model and previous findings [ 29 , 30 ]. According to the KAP model, dietary behavioral changes in HD patients involved three successive processes: knowledge acquisition, belief generation, and behavior formation.…”
Section: Discussionsupporting
confidence: 93%
“…The significant correlations observed suggest that increasing patients' knowledge could positively influence their attitudes and practices. This aligns with Alghamdi et al and Zhang et al [ 38 , 39 ], who reported that informed patients are more likely to engage in screening practices. These consistent associations across different studies underline the importance of educational interventions to improve screening uptake.…”
Section: Discussionsupporting
confidence: 89%
“…KAP assessment questionnaires have been developed and used in highly prevalent malignancies such as cervical, prostate and gastrointestinal cancers [ 22 – 24 ]. A Chinese cross-sectional study among healthcare workers found moderate knowledge and positive attitudes regarding early gastrointestinal cancers [ 24 ]. The presence of good knowledge and a positive attitude were found to correlate with excellent practice in this survey.…”
Section: Discussionmentioning
confidence: 99%